ISPD Catheter-related Infection Recommendations: 2023 Update. Issue 3 (May 2023) - Chow, Kai Ming; Li, Philip Kam-Tao; Cho, Yeoungjee; Abu-Alfa, Ali; Bavanandan, Sunita; Brown, Edwina A; Cullis, Brett; Edwards, Dawn; Ethier, Isabelle; Hurst, Helen; Ito, Yasuhiko; de Moraes, Thyago Proença; et al.
Peritoneal dialysis (PD) catheter-related infections are important risk factors for catheter loss and peritonitis. The 2023 updated recommendations have revised and clarified definitions and classifications of exit site infection and tunnel infection. A new target for the overall exit site infection rate should be no more than 0.40 episodes per year at risk. The recommendation about topical antibiotic cream or ointment to catheter exit site has been downgraded. New recommendations include clarified suggestion of exit site dressing cover and updated antibiotic treatment duration with emphasis on early clinical monitoring to ascertain duration of therapy. In addition to catheter removal and reinsertion, other catheter interventions including external cuff removal or shaving, and exit site relocation are suggested. Graphical Abstract This is a visual representation of the abstract.